Administration of income tax 2023 (Thomson Reuters, 2023)
"Administration of Income Tax, 2023 is a comprehensive treatment of the law governing the administration of federal income tax in Canada (and provincial income taxes administered by the CRA under collection agreements). It is written from a taxpayer's perspective and provides the framework for tax returns, payments, audits, assessments and reassessments, objections, and appeals."--Quatrième de couverture